Dermatomyositis presenting as heart failure revealed a concealed cervical malignancy: an infrequent clinical nexus. Issue 2 (28th February 2020) - Ghosh, Ritwik; Dubey, Souvik; Chatterjee, Subhankar; Biswas, Rakesh
Abstract : Dermatomyositis (DM) belongs to the spectrum of inflammatory myopathies which are a heterogeneous group of acquired disorders in which dysregulated immune system is thought to play a major pathologic role. Patients with DM generally present with characteristic skin manifestations with or without muscle weakness and pain. Although subclinical myocardial involvement in DM is well reported in literature, heart failure (HF) as its principal manifestation is extremely rare. Recognition of DM, a known paraneoplastic syndrome, should prompt clinicians to search for underlying malignancy. While gynaecological malignancies are common in association with DM, cervical cancer has rarely been heard of as an aetiology of paraneoplastic DM. We are reporting a case of DM in a postmenopausal woman presenting with advanced decompensated congestive HF with hidden squamous cell carcinoma of cervix.